The existence of Human resource development (HRD) on the development of employee creativity - Fahrul Kahfi (Journal of Management and Administration Provision, 2022)
Human Resource Development (HRD) is essential in encouraging originality among workers. Human resource development (HRD) efforts can help businesses create a workplace that values and rewards employees' unique contributions by instituting procedures for skill development, encouraging teamwork, and providing appropriate recognition and compensation. In addition, HRD can equip workers with the means they need to develop and implement their own innovative ideas. However, there are difficulties that must be surmounted before HRD can be implemented successfully and its impact on employees' inventiveness fully realized. Employees' unwillingness to adapt to new ways of doing things, scarce funds, and the challenge of gauging ROI all rank high on the list of barriers to effective human resource development. Despite these obstacles, a more innovative and productive workforce is possible through the deliberate and intentional application of HRD, which benefits the firm as a whole.